Freedom for some, but not for Mum: the reproductive injustice associated with pandemic ‘Freedom Day’ for perinatal women in the United Kingdom - Silverio, Sergio A.; Harris, Elizabeth J.; Jackson, Leanne; Fallon, Victoria, The PRaM Study Group; Easter, Abigail; Dadelszen, Peter von; Jurković, Davor; Magee, Laura A.; Soulsby, Laura K.; Christiansen, Paul; De Pascalis, Leonardo; et al. (Frontiers in Public Health, 2024)
Introduction: Healthcare services for pregnant and postpartum (‘perinatal’) women were reconfigured significantly at the advent and for the duration of the SARS-CoV-2 Pandemic and despite the United Kingdom announcing ‘Freedom Day’ on 19 July 2021 (whereafter all legal lockdown-related restrictions were lifted), restrictions to maternity (antenatal, intrapartum, and postnatal) services remained. This study presents data from eight perinatal women about their experiences of psychosocial wellbeing and maternity care in the post-‘Freedom Day’ epoch. Methods: Semi-structured interviews were conducted virtually, with data recorded, transcribed, and analysed by hand. Grounded Theory Analysis was employed with the final theory assessing the reproductive injustice of the pandemic ‘Freedom Day’. Results: Analysing iteratively and inductively led to four emergent themes: ‘A Failing System, Failing Women’; ‘Harm Caused by a State of Difference’; ‘The Privileges (Not Rights) of Reproductive Autonomy, Agency, and Advocacy’; and ‘Worried Women and Marginalised Mothers’. Together, these themes form the theory of: ‘Freedom for some, but not for Mum’. Discussion: Women experienced a lack of high-quality reliable information about the pandemic, vaccination against the virus, and the changes to, and decision-making surrounding, their perinatal care. Women recognised healthcare professionals and maternity services were stretched and that maternity services were failing, but often reported hostility from staff and abandonment at times when they were unsure about how to navigate their care. The most singular injustice was the disparity between women having to accept continuing restrictions to their freedom while receiving maternity care and the (reckless) freedom being enacted by the general public.